A Barrio ABC - Hudes, Quiara Alegria (USA, 2010)
A young girl takes a walk through her urban neighborhood, observing items representing every letter of the alphabet, from her abuela to loud, zooming cars...
Keywords: Alphabets; Concepts - ABC; Juvenile Literature